Analysis of Research in Human Capital Management Practices for Workforce Agility and Knowledge Sharing - Kurniawan, Erfan; Sudiarditha, I Ketut R; Yohana, Corry (IJHCM (International Journal of Human Capital Management), 2024)
This study aims to analyze the development of research in the field of Human Capital Management (HCM) with a particular emphasis on the constructs of Workforce Agility and Knowledge Sharing. Using a literature review approach, this study synthesizes findings from 30 Scopus-indexed articles published between 2019 and 2024. The analysis reveals that Workforce Agility and Knowledge Sharing play versatile roles in research models, functioning as independent, dependent, and mediating variables in relation to organizational outcomes. The findings also indicate that both constructs are strongly interconnected, where Workforce Agility enhances adaptive responses to dynamic environments, while Knowledge Sharing facilitates collective learning and innovation. Together, these two variables contribute to strengthening organizational competitiveness, productivity, and sustainable performance. The study highlights that incorporating Workforce Agility and Knowledge Sharing as strategic references within HCM practices provides valuable guidance for organizations in addressing uncertain, complex, and rapidly changing business contexts. Furthermore, the implications suggest that future research should explore more diverse methodologies and contexts to deepen the theoretical and practical understanding of their impact on organizational growth.